SISTEM INFORMASI PENERIMAAN SISWA BARU MENGGUNAKAN JAVA NETBEANS DAN DB MYSQL (Studi Kasus: MI AT– TAQWA Kedungtuban) - tiodora irnariyanti; Adhika Pramita Widyassari (SIMETRIS, 2018)
Registration and Admission of new students in MI AT-TAQWA Kedungtuban still uses the manual method in the form of filling in the registration form first and then moved to the ledger, slowing down time and writing errors often occur during the process of recording in the ledger. In addition, there are also often obstacles when the registrant form slips when it is submitted to the ledger. These constraints will cause the PSB committee to feel difficulties when inputting new students. The purpose of research, design, development, and the process of applying new student admissions using a Java NetBeans IDE-based information system. The design of information systems is modeled into diagrams in UML (Unified Modeling Language) and the method of developing the System Development Life Cycle (SDLC) with the Waterfall model. The test results of the New Student Admission Information System obtained 96% of the Interface tested well. The research data was taken from MI AT-TAQWA Kedungtuban in 2019/2020. This research can help the school to make maximum and accelerate registration and acceptance of new students to the maximum.